2017
DOI: 10.1371/journal.pone.0180337
|View full text |Cite
|
Sign up to set email alerts
|

Differences of immune disorders between Alzheimer’s disease and breast cancer based on transcriptional regulation

Abstract: Although chronic inflammation and immune disorders are of great importance to the pathogenesis of both dementia and cancer, the pathophysiological mechanisms are not clearly understood. In recent years, growing epidemiological evidence and meta-analysis data suggest an inverse association between Alzheimer’s disease (AD), which is the most common form of dementia, and cancer. It has been revealed that some common genes and biological processes play opposite roles in AD and cancer; however, the biological immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This evidence supports previous studies proposing its role as a tumor suppressor in various types of cancers [ 186 , 187 ]. In addition, altered expression of SPDEF has been found in Alzheimer’s disease patients and animal models, while a recent association was found between blood-based Spdef methylation and stress response, altered dopaminergic neurotransmission and increased vulnerability to substance abuse, suggesting its role as a biomarker for these pathological conditions [ 188 , 189 , 190 , 191 ].…”
Section: Cracking the Transcriptional Regulatory Programs Of Neuronal...mentioning
confidence: 99%
“…This evidence supports previous studies proposing its role as a tumor suppressor in various types of cancers [ 186 , 187 ]. In addition, altered expression of SPDEF has been found in Alzheimer’s disease patients and animal models, while a recent association was found between blood-based Spdef methylation and stress response, altered dopaminergic neurotransmission and increased vulnerability to substance abuse, suggesting its role as a biomarker for these pathological conditions [ 188 , 189 , 190 , 191 ].…”
Section: Cracking the Transcriptional Regulatory Programs Of Neuronal...mentioning
confidence: 99%
“…In recent years, epidemiological evidence of a controversial association between cancer and neurodegenerative diseases has been increasing. Common etiological factors may play opposing roles in the pathogenesis of neurodegeneration and breast cancer[ 14 , 15 ]. Characteristic brain pathology leads to neuronal cell death and neurodegeneration over time, whereas cancer is dominated by the process of unlimited cell proliferation[ 16 , 17 ].…”
Section: Breast Cancer Risk and Schizophreniamentioning
confidence: 99%
“…A different study showed that LPP was suppressed considerably in MCI samples in comparison with the healthy ones 60 . Another study named some of the genes that had regulation changes between healthy and AD samples and argued that LPP was one of them 61 . KLF13 was introduced in a neurodegenerative disease study as one of the key regulators in Alzheimer's disease 62 .…”
Section: Enrichment Analysismentioning
confidence: 99%